Neonatal brain oxygenation during thoracoscopic correction of esophageal atresia - Tytgat, Stefaan H. A. J. (Surg Endosc, 2015)
BACKGROUND: Little is known about the effects of carbon dioxide (CO(2)) insufflation on cerebral oxygenation during thoracoscopy in neonates. Near-infrared spectroscopy can measure perioperative brain oxygenation [regional cerebral oxygen saturation (rScO(2))]. AIMS: To evaluate the effects of CO(2) insufflation on rScO(2) during thoracoscopic esophageal atresia (EA) repair. METHODS: This is an observational study during thoracoscopic EA repair with 5 mmHg CO(2) insufflation pressure. Mean arterial blood pressure (MABP), arterial oxygen saturation (SaO(2)), partial pressure of arterial carbon dioxide (paCO(2)), pH, and rScO(2) were monitored in 15 neonates at seven time points: baseline (T0), after anesthesia induction (T1), after CO(2)-insufflation (T2), before CO(2)-exsufflation (T3), and postoperatively at 6 (T4), 12 (T5), and 24 h (T6). RESULTS: MABP remained stable. SaO(2) decreased from T0 to T2 [97 ± 3–90 ± 6 % (p < 0.01)]. PaCO(2) increased from T0 to T2 [41 ± 6–54 ± 15 mmHg (p < 0.01)]. pH decreased from T0 to T2 [7.33 ± 0.04–7.25 ± 0.11 (p < 0.05)]. All parameters recovered during the surgical course. Mean rScO(2) was significantly higher at T1 compared to T2 [77 ± 10–73 ± 7 % (p < 0.05)]. Mean rScO(2) levels never dropped below a safety threshold of 55 %. CONCLUSION: The impact of neonatal thoracoscopic repair of EA with insufflation of CO(2) at 5 mmHg was studied. Intrathoracic CO(2) insufflation caused a reversible decrease in SaO(2) and pH and an increase in paCO(2). The rScO(2) was higher at anesthesia induction but remained stable and within normal limits during and after the CO(2) pneumothorax, which suggest no hampering of cerebral oxygenation by the thoracoscopic intervention. Future studies will focus on the long-term effects of this surgery on the developing brain.